Influenza: special aspects in old age Influenza: besondere Aspekte im höheren Lebensalter - Kwetkat, A.; Leischker, A.; Heppner, Hans Jürgen (Zeitschrift für Gerontologie und Geriatrie, 2018)
In Germany up to 20% of the population are affected by influenza every year. Particularly for the elderly, influenza is related to high morbidity and mortality and 90% of deaths are related to the group of 60 years and older. In this context, seasonal influenza caused by influenza A (H3N2) viruses is exceedingly relevant for the elderly. The aging of the immune system, immunosenescence, is well documented as the cause of increased susceptibility to infection and change of typical symptoms. This can cause a delay in diagnosing and treatment of influenza infections. Furthermore, immunosenescence can lead to decreased efficacy of vaccination. Adjuvanted vaccines and vaccines with higher antigen content cause an enhanced immune response and are therefore especially suitable for prevention. The Standing Vaccination Committee (STIKO) recommends vaccination against seasonal influenza for all persons 60 years of age and over as well as for nursing home residents, pregnant women and chronically ill patients. For the coming influenza season 2018/19, the STIKO generally recommends the administration of quadrivalent (tetravalent) vaccines for the first time.
CRIS-Team Scopus Importer:2022-09-26
Keywords: Immunologic adjuvants; Immunosenescence; Orthomyxoviridae; Quadrivalent influenza vaccine; Recommendations; health planning